ANALISIS HOLISTIK MOTIVASI KERJA GURU TK - Satria, Rachmat; Muhammad, Al Fadil; Faradila, Nurul; Muslim, Inayatillah; Putri, Aurellia Nailah (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2025)
This study aims to comprehensively analyze the intrinsic and extrinsic factors influencing the work motivation of teachers at TK IT Bazla, an integrated Islamic early childhood education institution in Indonesia. Employing a phenomenological approach, the research explores teachers' experiences and perceptions regarding their professional motivation. Data were collected through in-depth interviews with six participants and analyzed qualitatively. The findings reveal that intrinsic motivation is primarily driven by love for children, a strong belief in the institution's mission, and a desire for personal growth. On the other hand, extrinsic factors such as support from leadership, colleagues, and parents significantly enhance motivation. However, challenges in dealing with parents were identified as a key obstacle. This study underscores the importance of a holistic approach to fostering teacher motivation by integrating internal drive with a supportive work environment. The results contribute to both theoretical understanding and practical strategies for improving teacher performance and well-being, ultimately enhancing the quality of early childhood education at TK IT Bazla.